Cutting Camp with Killing: 'Bad' Feelings, Refusing Respectability, and Homeopathic Camp. (March 2018) - Morrison, Josh
Abstract : This essay argues that Ticked-Off Trannies with Knives (dir. Israel Luna, 2010, hereafter TOTWK ) uses homeopathic trans camp to re-mediate the phobic traumas that trans people face. TOTWK reworks its exploitation cinema aesthetic roots, turning traumas committed against trans people and the 'bad' feelings they espouse into homeopathic methods of healing trans bodies, both cinematic and material, through the practice of introjection. Building on philosophies of homeopathy and theories of body camp TOTWK explicates new modes of working through trauma that do not conform to individualistic social norms or to LGBT respectability politics, decentering medicalized, pathologized narratives of transition and trans embodiment.